Counteraction to investigation of raiding criminal offenses: common forms and peculiarities of addressing - Tiulieniev, Serhii (Archives of Criminology and Forensic Sciences, 2024)
Taking into account the needs of law application practice in the context of countering raiding criminal offenses, the Article Purpose is to identify common forms of countermeasures to the investigation of raiding criminal offenses and determine possible methods of countering such crimes. Stemming from the results of theoretical sources study and processing of empirical material, it has been established that organization measures to address counteraction to investigation of raiding criminal offenses should be based on the study of current crime trends, and be carried out in conformity with provisions of the Law and the use of efficient tactical techniques and methods developed by criminal procedure and criminalistics. Traditionally, the ways for addressing counteraction to investigation include: individual investigative (search) actions; tactical operations; organizational and tactical measures of an operational search nature. It has been pointed out that common forms of countering investigation utilized by raiders are: 1) destruction of physical and digital traces of unlawful activities; 2) application of psychological pressure measures against participants to criminal proceedings, as well as the use of physical violence or threats of such measures; 3) failure to provide reliable information about criminal event (implemented, as a rule, in three models); 4) avoiding participation in procedural actions; 5) hiding from pre-trial investigation agencies, etc. We are of the opinion that prospects for subsequent research lie in the development of algorithms for procedural actions to ad-dress counteraction depending on typical investigative situations in which it is carried out.